Assessment of different turbulence models in simulating axisymmetric flow in suddenly expanded nozzles - Khan, Sher Afghan; Ali, Mir Owais; Riyadh, Miah Mohammed; Hossen, Zahid; Arefin, Nafis Mahdi (Science Publishing Corporation, 2018)
A numerical simulation was carried out to compare various turbulence models simulating axisymmetric nozzle flow past suddenly ex-panded ducts. The simulations were done for L/D = 10. The convergent-divergent nozzle has been modeled and simulated using the turbu-lence models: The Standard k-ε model, The Standard k-ω model and The SST k-ω model. Numerical simulations were done for Mach numbers 1.87, 2.2, and 2.58 and the nozzles were operated for NPRs in the range from 3 to 11. From the numerical analysis it is apparent that for a given Mach number and effect of NPR will result in maximum gain or loss of pressure. Numerical results are in good agreement with the experimental results.